DNA Nanostructure as an Efficient Drug Delivery Platform for Immunotherapy - Chi, Qingjia; Yang, Zichang; Xu, Kang; Wang, Chunli; Liang, Huaping (Frontiers in Pharmacology, 2020)
Immunotherapy has received increasing attention due to its low potential side effects and high specificity. For instance, cancer immunotherapy has achieved great success. CpG is a well-known and commonly used immunotherapeutic and vaccine adjuvant, but it has the disadvantage of being unstable and low in efficacy and needs to be transported through an effective nanocarrier. With perfect structural programmability, permeability, and biocompatibility, DNA nanostructures are one of the most promising candidates to deliver immune components to realize immunotherapy. However, the instability and low capability of the payload of ordinary DNA assemblies limit the relevant applications. Consequently, DNA nanostructure with a firm structure, high drug payloads is highly desirable. In the paper, the latest progress of biostable, high-payload DNA nanoassemblies of various structures, including cage-like DNA nanostructure, DNA particles, DNA polypods, and DNA hydrogel, are reviewed. Cage-like DNA structures hold drug molecules firmly inside the structure and leave a large space within the cavity. These DNA nanostructures use their unique structure to carry abundant CpG, and their biocompatibility and size advantages to enter immune cells to achieve immunotherapy for various diseases. Part of the DNA nanostructures can also achieve more effective treatment in conjunction with other functional components such as aPD1, RNA, TLR ligands.